ENHANCING EFL GRAMMAR LEARNING THROUGH GAME-BASED LEARNING: A SYSTEMATIC LITERATURE REVIEW - Novi Intan Aprilia; Duratun Nasekhah (JEELL (Journal of English Education, Linguistics and Literature), 2025)
This systematic literature review investigates the effectiveness of game-based learning (GBL) in enhancing English as a Foreign Language (EFL) students’ grammar mastery. By analyzing eleven selected peer-reviewed studies published between 2015 and 2025, the review explores how digital games support grammar instruction through interactive features, instant feedback, and student-centered design. The findings indicate that GBL significantly increases student motivation, engagement, and performance, especially when aligned with learners’ proficiency levels and interests. However, challenges such as digital literacy gaps, access to infrastructure, and emotional stress due to competitive elements must be addressed. This review highlights the need for thoughtful game selection and teacher facilitation to ensure inclusive and effective grammar instruction through GBL.